Assessing the modifiable and non-modifiable risk factors associated with multimorbidity in reproductive aged women in India - Priya Das; Subhadeep Saha; Tanu Das; Partha Das; Tamal Basu Roy (BMC, 2024)
Abstract Background Reproductive span is the foundation of every woman's health in later life. India is currently facing a growing burden of multiple morbidities among the women in their reproductive age group which may further increase over the coming decades. The purpose of the present study aimed to identify different modifiable and non-modifiable risk factors affecting multimorbidity among the women in reproductive age group in Indian context. Methods Secondary data were obtained from the Demography and Health Survey (DHS), conducted in India during 2019-2021. A total of 671,967 women aged 15-49 years were selected for this present study. Descriptive, association studies and multinominal logistic regression analyses were performed to accomplish the objectives. Results Currently, 6.3% of total study participant's reproductive age group women suffered from multimorbidity in India. Never consuming protein, fruits, vegetables and milk increase the chances of developing multimorbidity. Consumption of fried foods, aerated drinks and addiction towards tobacco and alcohol also has a greater influence on the prevalence of multimorbidity. The prevalence of multimorbidity is sharply increased with increasing age and Body Mass Index (BMI). Regionally, the prevalence of multimorbidity was found more among the women hailed from eastern and north-eastern India. Conclusion To reduce the risk of developing multimorbidity, targeted interventions are needed in the form of educating every woman concerning the importance of having minimum health-related knowledge, maintaining healthy lifestyle, weight management and having proper and balanced diet.